6x-2x+11=5

Simple and best practice solution for 6x-2x+11=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-2x+11=5 equation:



6x-2x+11=5
We move all terms to the left:
6x-2x+11-(5)=0
We add all the numbers together, and all the variables
4x+6=0
We move all terms containing x to the left, all other terms to the right
4x=-6
x=-6/4
x=-1+1/2

See similar equations:

| 0.4y+2.9=1.5 | | 4^(1+2x)=1024 | | x2-9x-5=0 | | 8v+2-6v=9+v | | 4(3x+2)-11=8 | | 2+6g=11=3g | | 5(x—3)+22=57 | | -9=-4w | | 3x+8-x=2x+1 | | -12=-3/5v | | x2+2x-360=0 | | t−23.5=−39.7 | | -3(q+38)=-21 | | 2(x-4)=4x3x+6 | | -4+2k=-6(-6-2k) | | 4x+7=2x+8-5 | | (3x-13)+(x-3)=180 | | (4n+17)+(3n+16)=180 | | x−(−7)=5 | | 3x^2+1=73 | | 5x2-10x=0 | | 5x-8+1=-4x-7+7x | | 10=6=2u | | 162-12y/24+4y=43 | | 4x2-4x=0 | | (5y)+110=180 | | 0.9-0.4z=5.7 | | 2(7y−1)=40 | | 1=2j=9 | | 2(-5+4p)=-2(5+3p) | | 1/4c+3/4=-1/2 | | 18x2-29x+3=0 |

Equations solver categories